The Moody Handbook of Theology - Enns, Paul (Chicago Moody Press, 1989)
Moody Handbook of Theology has been written as a general introductory work in the area of theology than can provide answers to simple, basic questions. Its intended audience is not only Bible institute, college, and seminary students, but also Sunday sc
Keywords: Theology -- Handbooks, manuals, etc. Fundamentalism -- Handbooks, manuals, etc. Dispensationalism -- Handbooks, manuals, etc